Peranan model pembelajaran “bertukar pasangan” pada keterampilan berbicara - Burhanuddin Burhanuddin; Hasmawati Hasmawati; Muddin Muddin (Seminar Nasional LP2M UNM, 2019)
The purpose of this study was to determine the effectiveness of the partner exchange learning model to improve students' speaking skills. The approach used in this study is quasi experiment. Data collection techniques consist of learning outcomes tests, interviews and observations. The population in this study were students of Madrasah Aliyah (MA) in Takalar district. Data analysis techniques used are inferential statistics and descriptive statistics. Based on the results of the research and discussion conducted, it can be concluded that the role of the "Swapping Pair" learning model in improving students' speaking skills is very large. This is evidenced from the results of tests of speaking skills of students as a whole in the first cycle reached 68.75%, and in the second cycle increased to 76.33%.